2022
DOI: 10.3390/cells11050796
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacies of Berberine against Neurological Disorders: An Update of Pharmacological Effects and Mechanisms

Abstract: Neurological disorders are ranked as the leading cause of disability and the second leading cause of death worldwide, underscoring an urgent necessity to develop novel pharmacotherapies. Berberine (BBR) is a well-known phytochemical isolated from a number of medicinal herbs. BBR has attracted much interest for its broad range of pharmacological actions in treating and/or managing neurological disorders. The discoveries in basic and clinical studies of the effects of BBR on neurological disorders in the last de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 176 publications
0
7
0
Order By: Relevance
“…Berberine being a NRF2/ARE pathway activator demonstrates therapeutic effects against many chronic diseases, such as obesity, diabetes, inflammatory bowel disease, atherosclerosis, and cardiovascular diseases, due to its multiple-target effects [ 84 ]. Specifically, berberine has been shown to activate NRF2/ARE signaling and exert cytoprotection in non-alcoholic fatty liver disease [ 85 ], and many neurological and metabolic diseases [ [86] , [87] , [88] ]. In healthy male humans, repeated administration of berberine decreased CYP2D6, CYP2C9, and CYP3A4 [ 89 ] compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Berberine being a NRF2/ARE pathway activator demonstrates therapeutic effects against many chronic diseases, such as obesity, diabetes, inflammatory bowel disease, atherosclerosis, and cardiovascular diseases, due to its multiple-target effects [ 84 ]. Specifically, berberine has been shown to activate NRF2/ARE signaling and exert cytoprotection in non-alcoholic fatty liver disease [ 85 ], and many neurological and metabolic diseases [ [86] , [87] , [88] ]. In healthy male humans, repeated administration of berberine decreased CYP2D6, CYP2C9, and CYP3A4 [ 89 ] compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Further scrutiny revealed that 39 chemical components, including berberine, baicalin, palmatine, nobiletin, neochlorogenic acid, quercetin, luteolin, catechin, kaempferol, glycitein, wogonin, rotundine, mollugin, and xyloidone, met the screening criteria and could serve as effective components of drugs. For instance, berberine shows promise in preventing GA and reducing inflammatory responses due to its anti-inflammatory, antibacterial, neuroprotective, and immune-regulating properties [ [24] , [25] , [26] , [27] ], and can reduce the expression of inflammatory factors such as MMP-9, TNF-α, and IL-6 [ 28 ]. Baicalin, sourced from the root of Scutellaria baicalensis, possesses beneficial effects such as anti-viral, anti-bacterial, and anti-oxidative properties [ [29] , [30] , [31] ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations have demonstrated that, beyond its longstanding attributed properties, berberine exerts a multifaceted influence on regulating numerous molecular pathways. Studies report evidence of therapeutic use on digestive, cardiovascular, neurological, metabolic, and endocrine diseases [20][21][22][23][24][25][26][27][28][29][30][31][32]. Scientists are currently investigating the potential of berberine as a therapeutic agent for the management of hormonal imbalances.…”
Section: Berberine -A Molecular Mechanism Of Action In Hyperandrogenismmentioning
confidence: 99%